Restructuring Regulation of the Railroad Industry - Kessides, Ioannis N.; Willig, Robert D. (World Bank, Washington, DC, 2012)
Throughout the world, the rail industry has been one of the most heavily regulated sectors. The public utility paradigm of government regulation has failed to handle the central regulatory problem--the mixture of competive and monopoly elements in supply-- and is now being blamed for the poor financial condition of the railroads, for the deterioration of rail plant, for the lack of innovation, and for the mediocre quality of rail services. This Note outlines a set of principles, called constrained market pricing, for regulatory reform in the public interest and considers their implications for railroad restructuring.